2017
DOI: 10.1080/19396368.2017.1393583
|View full text |Cite
|
Sign up to set email alerts
|

Sperm RNA elements as markers of health

Abstract: GO: Gene Ontology; ART: assisted reproductive technology; IVF: in vitro fertilization; ICSI: intra-cytoplasmic sperm injection; RNA-seq: RNA-sequencing; TIC: timed intercourse; IUI: intrauterine insemination; SRE: sperm RNA elements; HPA: Human Protein Atlas; SMDS: sedaghatian-type spondylometaphyseal dysplasia; DBA: Diamond-Blackfan anemia; RPKM: reads per kilobase per million; TPM: transcripts per million; IPA: Ingenuity Pathway Analysis; OMIM: Online Mendelian Inheritance in Man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 79 publications
(115 reference statements)
0
19
0
Order By: Relevance
“…We have previously identified sperm RNAs required for live birth [30]. Gene ontology along with developmental and disease associations of sperm RNAs and DNA methylation analyses suggest a potential impact on child health and development [29,31,32]. We sought to define the relationship between obesity as measured by BMI and human sperm RNAs to expand our understanding garnered from animal models of obesity [33,34] and other human studies [4,29,35].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified sperm RNAs required for live birth [30]. Gene ontology along with developmental and disease associations of sperm RNAs and DNA methylation analyses suggest a potential impact on child health and development [29,31,32]. We sought to define the relationship between obesity as measured by BMI and human sperm RNAs to expand our understanding garnered from animal models of obesity [33,34] and other human studies [4,29,35].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, it has been well established that Ndrg1 exerts an inhibitory effect on cancer cell proliferation (Chang et al, 2014;McCaig et al, 2011;Xi et al, 2017;Zhang et al, 2019). Additionally, several studies have shown that Ndrg1 is expressed in the gonads of humans, mice, sheep and medaka (Burl et al, 2018;Kikuchi et al, 2019;Lachat et al, 2002;Qu et al, 2019;Stévant and Nef, 2019), however its role in gonadal function and reproduction is still unknown. In medaka, there are two paralogs of ndrg1: ndrg1a and ndrg1b, although only ndrg1b is expressed in the gonad.…”
Section: Discussionmentioning
confidence: 99%
“…There are no treatments currently available for defects in the RNAs that are reflective of disease, but it does provide a mechanistic understanding of the basis of infertility [77][78][79]. RNA content may be a predictor of human health and could be used to monitor the impact and recovery from environmental exposures [80,81]. As a result, assessing sperm RNA has the potential to evaluate the father's contribution, his current health status, and the health of his future child [80].…”
Section: Rna-sperm Transcriptsmentioning
confidence: 99%
“…RNA content may be a predictor of human health and could be used to monitor the impact and recovery from environmental exposures [80,81]. As a result, assessing sperm RNA has the potential to evaluate the father's contribution, his current health status, and the health of his future child [80].…”
Section: Rna-sperm Transcriptsmentioning
confidence: 99%